FPGA based advanced control of high frequency power converter - Ji, Xinlei (2019)
As a result of the rapid development of integrated circuits and power electronics technology, the control technology of power converters is being enhanced. The chip design based on EDA technology is becoming the mainstream of electronic system design and providing a new effective method for digital control of power converters, which also provides a basis for the control of power converters based on FPGA (field programmable gate array). This dissertation uses the DE1-SoC board designed by Altera Corporation as the comprehensive development platform. Also, it uses SOPC technology and embeds the soft core Nios II as the central processor in the FPGA. At the same time, the control of the entire high-frequency power converter circuit is realized by the Avalon bus, thereby realizing the high frequency control of the power converter. It greatly enhances the controller capability for the power converter compared to the conventional microcontroller or digital signal processor (DSP) based control system. This dissertation analyzes the design process of the software and hardware of the control system in detail. In hardware part, it first describes the overall hardware design procedure, and then describes the specific scheme of each functional module, including FPGA, Flash and PWM modules. The PWM and the ADC module are written by using Verilog HDL to generate interface function modules. In the software part, the design of the overall system is also discussed first, followed by a detailed description of the design flow of each functional module. The control algorithm of the power converter is based on the floating-point, and the parameters are determined according to values of sampled signal. Finally, it is coded using the C language and downloaded into the Nios II to control the converter to obtain the experiment result.